2015
DOI: 10.1155/2015/501878
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Method for Eliminating Spin Losses in Toroidal Traction Drives

Abstract: The efficiency of the original Toroidal continuously variable transmission (CVT) is limited due to the spin losses caused by the different speed distribution in the contact area. To overcome this drawback, this paper replaces the original working surface with a new surface derived from a differential equation and proposes a novel Logarithmic CVT. Equations and ranges of the transmission ratio range, half-cone-angle, and conformity ratio, which are essential geometrical parameters of the Logarithmic CVT, are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…A large number of studies [9][10][11][12] have shown that spin losses affect the traction performance of t-CVT significantly. Therefore, decreasing the spin losses can improve the reliability and fatigue life [13] , increase the power density and torque capacity [7,14] , and greatly improve the traction efficiency of traction CVT [15][16][17] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies [9][10][11][12] have shown that spin losses affect the traction performance of t-CVT significantly. Therefore, decreasing the spin losses can improve the reliability and fatigue life [13] , increase the power density and torque capacity [7,14] , and greatly improve the traction efficiency of traction CVT [15][16][17] .…”
Section: Figurementioning
confidence: 99%
“…Then, a novel double roller Full-Toroidal CVT(FT-CVT) was designed by Novellis et al [17] , and this type of CVT can also significantly decrease the spin losses. However, the most representative research was the zero-spin design methodology developed by Li et al [15,16] . The core idea of this methodology was that the original working surface of drive or driven components were redesigned to satisfy the zero-spin condition mentioned above.…”
Section: Figurementioning
confidence: 99%
“…It should be limited or eliminated in design due to its energy loss. Although the generatrix of the traction component has been redesigned to replace the circular generatrix and realizing zero-spinning theoretically (Li et al, 2019;Li et al, 2015aLi et al, , 2015b, it is also intractable for the new generatrix to be expressed by primary functions and manufactured. Therefore, the usual mean to limit the spin loss for improving efficiency is reducing the contact angle, which is also adapted in the proposed structure.…”
Section: Spin Analysismentioning
confidence: 99%
“…A large number of studies [9][10][11][12] have shown that spin losses affect the traction performance of t-CVT significantly. Therefore, decreasing the spin losses can improve the reliability and fatigue life [13] , increase the power density and torque capacity [7,14] , and greatly improve the traction efficiency of traction CVT [15][16][17] .…”
Section: Figurementioning
confidence: 99%